CORRELATION OF CANVA AI WITH WRITING SKILL AND VOCABULARY MASTERY OF DESCRIPTIVE TEXT FOR DEAF STUDENTS CLASS VII AT SLB HAMONG PUTRO JOMBOR SUKOHARJO - Sujito; Vinna Mei Astuti (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This research was conducted to analyze multivariate correlational relationship among using canva ai (artificial intelligence) features, writing descriptive text skill, and vocabulary mastery of class vii deaf students in slb hamong putro jombor sukoharjo. This study adopted a quantitative correlational research design, and the sample consisted of four students, using a intensive case study approach. The data was gathered through observation on canva ai utilization, descriptive text writing skill tesr, and vocabulary mastery test. Data were processed by employing multiple correlation and partial correlation. Hypothetical results predict a significant positive relationship between the collective use of Canva AI and students writing skills and vocabulary mastery (R = 0.85; p < 0.05). In part, using canva ai correlated strongly to writing skills (r = 0.78) and moderately to vocabulary mastery (r = 0.62). The research findings imply that visual and text-based interactive features of Canva AI which address learning requirements for deaf students, can be considered as promising new learning media to develop their literacy and languag e competence particularly in the sphere of descriptive text.